ApoE-functionalization of nanoparticles for targeted brain delivery: a feasible method for polyplexes? - Hartl, Natascha Verena; Gabold, Bettina; Uhl, Philipp; Kromer, Adrian; Xiao, Ximian; Fricker, Gert; Mier, Walter; Liu, Runhui; Merkel, Olivia (Drug Delivery and Translational Research, 2023)
The blood-brain barrier (BBB) poses a major obstacle in the treatment of all types of central nervous system (CNS) diseases. Small interfering RNA (siRNA) offers in principle a promising therapeutic approach by downregulating disease-related genes via RNA interference. However, the BBB is a formidable barrier for macromolecules such as nucleic acids. In an effort to develop a brain-targeted strategy for siRNA delivery systems formed by electrostatic interactions with cationic polymers (polyplexes (PXs)), we investigated the suitability of the well-known surfactant-based approach for Apolipoprotein E (ApoE)-functionalization of nanoparticles (NPs). The aim of this present work was to investigate if ApoE coating of siRNA PXs formed with cationic branched 25-kDa poly(ethyleneimine) (b-PEI) and nylon-3 polymers without or after precoating with polysorbate 80 (PS 80) would promote successful delivery across the BBB. We utilized highly hydrophobic NM0.2/CP0.8 nylon-3 polymers to evaluate the effects of hydrophobic cyclopentyl (CP) subunits on ApoE binding efficacy and observed successful ApoE binding with and without PS 80 precoating to the nylon-3 but not the PEI polyplexes. Accordingly, ApoE-coated nylon-3 polyplexes showed significantly increased uptake and gene silencing in U87 glioma cells but no benefit in vivo. In conclusion, further optimization of ApoE-functionalized polyplexes and more sophisticated in vitro models are required to achieve more successful in vitro-in vivo translation in future approaches.